Mechanisms of Pyrite Formation Promoted by Sulfate-Reducing Bacteria in Pure Culture - Duverger, Arnaud; Berg, Jasmine S.; Busigny, Vincent; Guyot, François; Bernard, Sylvain; Miot, Jennyfer (Frontiers in Earth Science, 2020)
Pyrite, or iron disulfide, is the most common sulfide mineral at Earth’s surface and is widespread through the geological record. Because sulfides are mainly produced by sulfate-reducing bacteria (SRB) in modern sedimentary environments, microorganisms are assumed to drive the formation of iron sulfides, in particular pyrite. However, the exact role played by microorganisms in pyrite formation remains unclear and, to date, the precipitation of pyrite in microbial cultures has only rarely been achieved. The present work relies on chemical monitoring, electron microscopies, X-ray diffraction and synchrotron-based spectroscopy to evaluate the formation of iron sulfides by sulfate-reducing bacteria Desulfovibrio desulfuricans as a function of the source of iron, either provided as dissolved Fe2+ or as FeIII-phosphate nanoparticles. Dissolved ferrous iron led to the formation of increasingly crystalline mackinawite (FeS) with time, encrusting bacteria cell walls, hence preventing further sulfate reduction upon day 5 and any evolution of iron sulfides into more stable phases, e.g. pyrite. In contrast, ferric phosphate was transformed into a mixture of large flattened crystals of well crystallized vivianite (Fe3(PO4)2 . 8 H2O) and a biofilm-like thin film of poorly crystallized mackinawite. Although being hosted in the iron sulfide biofilm, most cells were not encrusted. Excess-sulfide delivered by the bacteria and oxidants (such as polysulfides) promoted the evolution of mackinawite into greigite (Fe3S4) and the nucleation of pyrite spherules. These spherules were several hundreds nanometer wide and occurred within the extracellular polymeric substance (EPS) of the biofilm after only 1 month. Altogether, the present study demonstrates that the mineral assemblage induced by the metabolic activity of SRB strongly depends on the source of iron, which has strong implications for the interpretation of the presence of pyrite and vivianite in natural environments.